Antiviral activity of mink interferon alpha expressed in the yeast Pichia pastoris - Zhang, Hailing; Zhang, Dongliang; Lu, Han; Zou, Deying; Hu, Bo; Lian, Shizhen; Lu, Shiying (Frontiers in Veterinary Science, 2022)
Many viruses can cause infections in mink, including canine distemper virus, mink enteritis virus, and Aleutian disease virus. Current treatments are ineffective, and these infections are often fatal, causing severe economic losses. As antiviral drugs may effectively prevent and control these infections, recent research has increasingly focused on antiviral interferons. Herein, the gene encoding a mature mink interferon alpha (MiIFN-α) was synthesized according to the P. pastoris preference of codon usage and a recombinant plasmid, pPICZαA-MiIFN-α, was constructed. pPICZαA-MiIFN-α was linearized and transformed into the P. pastoris X33 strain, and zeocin-resistant transformants were selected. Protein expression was induced by methanol. SDS-PAGE and western blot analyses showed that a 25-kDa fusion protein was expressed in the culture supernatant. Antiviral activity of the expressed protein was determined using cytopathic effect inhibition (CPEI). The purified MiIFN-α significantly inhibited the cytopathic effect of vesicular stomatitis virus with a green fluorescent protein (VSV-GFP) in F81 feline kidney cells, with an antiviral activity of 6.4 × 107 IU/mL; it also significantly inhibited MEV replication in F81 cells. MiIFN-α antiviral activity against VSV-GFP was significantly reduced on treatment with pH 4 and pH 10 conditions for 24 h (p < 0.01). Serum MiIFN-α concentrations in rat were measured using enzyme-linked immune-sorbent assay; MiIFN-α concentrations in rat serum peaked at 36 h after injection. A high dose of MiIFN-α was safe for use. There were no significant differences in body temperature, tissue changes, and lymphocyte, total white blood cell, and central granulocyte counts between the injected and control groups (p > 0.05). These findings lay a foundation for the large-scale production of recombinant MiIFNs.